Aktivitas Corporate Social Responsibility (CSR) dan Publisitas Media: Dampaknya terhadap Citra Perusahaan dan Minat Beli (Studi Kasus: Konsumen Aqua Kelas Menengah ke Atas di Kota Semarang) - Septiani, Karen Arum; Prabawani, Bulan; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2016)
This research aims to determine whether the model of this research is acceptable or not. The model of this research is testing the effect of corporate social responsibility and media publicity toward purchase intention of consumer through corporate image as intervening variable. Data collection techniques used in this research was purposive sampling with 100 respondents as data samples. The data analysis was done quantitatively by using WarpPLS 3.0 software. The method analysis used were outer model, inner model, direct effect, indirect effect, Variance Accounted For (VAF) methods, and model of indicates. The result showed that model of this research was acceptable. The direct effect and indirect effect in this research were proven to give an significant effect. According to VAF method showed that the corporate image was included in partial mediation. The output model of indicate showed that the model already fulfill the goodness of fit.